Hearing loss among patients on treatment for drug-resistant tuberculosis in Uganda - Lodiong Jackson Dumo Lodiong; Timbine Amos; Boniface Amanee Elias Lumori; Edwin Nuwagira (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
Introduction: Second-line injectable therapy using aminoglycosides (AG) like kanamycin, amikacin or capreomycin is associated with irreversible hearing loss. We aimed to determine the incidence and predictors of hearing loss among patients with drug resistant tuberculosis (DR-TB) who received AG. Method: This was a retrospective cohort study conducted at the tuberculosis treatment unit of Mbarara Regional Referral Hospital (MRRH). All adult patients with a diagnosis of DR-TB between March 2016 and December 2019 were candidates for inclusion in the study. Hearing loss was defined as a hearing threshold of >20 decibels (dB) at any test frequency in at least one ear. The incidence and predictors of hearing loss were analysed using multivariable Cox model. A p-value of ≤0.05 was considered as statistically significant. Data analysis was done using STATA version 13. Results: The estimated rate of developing hearing loss was 107 per 1000 person months. Thirty-seven (52.9%) of 70 DR-TB patients experienced some degree of hearing loss, of which 25 (67.6 %) developed mild, 5 (13.5%) moderate, and 3 (8.1%) severe hearing loss. Male sex (HR 2.05, CI 1.03-4.10, p-value 0.041), increasing age (HR.5.17, CI 1.42-18.87, p-value 0.013) and high BMI (HR 3.31, CI 1.15 - 9.53, p-value 0.026) were significant predictors of new onset of hearing loss. Conclusion: The incidence of hearing loss among DR-TB patients was high, with the majority having a mild hearing loss. Patients who were male, older, overweight and/or obese were more likely to develop AG-induced hearing loss.